The dining culture and its well-being: a case study of the Indians in Klang Valley, Malaysia - Muniandy, Tamil Arasi; Subaramaniam, Kavitha; M. Vanugopal, Asha; Wan Nawi, Wan Norfadillah (2023)
Dining culture in Malaysian society has undergone a tremendous transformation in the past decades. The growing popularity of eating out has unwittingly contributed to Malaysia's food and beverage sector. Additionally, the hectic work schedule compels many people to spend numerous hours outside of their homes, forcing them to dine out. Hence, due to the variety of options available and the frantic urban lifestyle, eating out is accepted by the present society. However, Indian culture and their traditional medicine, Ayurveda, endorse "unnave marethu, marethey unuvu," which means ‘food is medicine, and medicine is the food’. Hence, one must exercise caution when making dietary selections for their daily meals. What they eat matters and helps them stay healthy. Meanwhile, a person's diet is regarded as an integral part of their wellbeing. As such, it is difficult to choose and obtain food that is truly nutritious, suits our health, and conforms to cultural expectations. Therefore, this study is carried out to investigate the wellbeing of Indians in the context of factors influencing them to dine out and the relationship of dining-out culture with their wellbeing. Quantitative research methodology was utilized to collect the data. Questionnaires were prepared according to the Likert scale measurement and will be distributed to 100 respondents via Google Form. The samples are based on a random sampling technique of Indians who are residing in Klang Valley. The data that is gathered will use the descriptive analysis method of the Statistical Package for Social Sciences (SPSS). The outcome of these findings will describe the factors influencing the Klang Valley Indians to dine out and its relationship with their wellbeing.